2008
DOI: 10.1021/jp803334b
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Symmetry Breaking in the Soai Reaction

Abstract: A kinetic model of spontaneous amplification of enantiomeric excess in the autocatalytic addition of diisopropylzinc to prochiral pyrimidine carbaldehydes is extended by a negative feedback process. Simulations based on the extended model result in large-amplitude oscillations both in a continuous-flow stirred tank reactor (CSTR) and in a semibatch configuration under optimized initial conditions. When sustained oscillations are maintained in a CSTR, no enantiomeric product distribution could be observed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 31 publications
3
40
0
2
Order By: Relevance
“…Mickskei et al [22] subsequently extended this idea to a detailed model and showed in numerical simulations that enantiomeric enrichment and oscillation can occur under appropriate conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Mickskei et al [22] subsequently extended this idea to a detailed model and showed in numerical simulations that enantiomeric enrichment and oscillation can occur under appropriate conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This effect primarily depended on the details of the numerical integrator used and was a consequence of the dynamic instability of the studied kinetic scheme. Micskei et al made very similar observations [66] while studying an oscillatory model of the Soai reaction in a semibatch reactor. They proposed that the inherent numerical error of the integrator method might be a model of the statistical fluctuations.…”
mentioning
confidence: 65%
“…The quantity of these structures in the usual range of micropreparative laboratory practice, from millimol to femtomol sample sizes, could reach such levels, which are higher than the sensitivity threshold of the asymmetric autocatalysis towards chiral induction, demonstrated experimentally [16][17][18][19][20] and evaluated theoretically [21][22][23][24]. In the relevant literature, however, no experimental or theoretical effort has been published earlier that deals with this problem.…”
Section: Discussionmentioning
confidence: 99%
“…These data show that even if the expectable e.e. values are very low, according to experimental evidence [16][17][18][19][20] and theoretical considerations [21][22][23][24], the isotope chirality in the tert.-butyl group in compounds 1 and/or 3 could influence the outcome of the most sensitive variant of the Soai reaction, however, taking into regard that it is separated from the pyrimidyl unit by the rigid C 2 moiety, and thus from the decisive molecular events around the new stereocenter, this option appears as scarcely probable, but cannot be excluded.…”
Section: The Tert-butyl Groupmentioning
confidence: 99%
See 1 more Smart Citation